Evaluation of an emergency room in operation during the COVID-19 pandemic: diagnoses and recommendations concerning environmental factors - Soares, Vitória Sanches Lemes; Ornstein, Sheila Walbe; França, Ana Judite Galbiatti Limongi (Frontiers in Built Environment, 2024)
To optimize the emergency room environment, this article puts forward comprehensive diagnoses and recommendations to minimize healthcare-associated infections. Emergency rooms are usually the initial point of entry into the healthcare system for individuals with different illnesses and needs. These environments frequently operate at maximum capacity, which result in challenges related to spatial organization. Therefore, a Post-Occupancy Evaluation was conducted within such an environment during the COVID-19 pandemic, utilizing a combination of qualitative and quantitative data collection methods. The following methodologies were employed to achieve the research objectives and scope: semi-structured interviews with staff members and a specialized architect; walkthrough accompanied by key individuals; behavior observation for flow mapping and quantification; visual records and physical surveys; measurements of environmental conditions and computational fluid dynamics simulations. The obtained results show the significance of maintaining and monitoring environmental conditions in specific environments; ensuring the appropriate allocation of hospital sectors; leveraging technology to reduce the exchange of paper among professionals; employing video calls to receive patients with flu symptoms; and implementing segregated patient-staff flow. Conclusively, these diagnoses and recommendations hold the potential to not only enhance the built environment of the case study but also to benefit other facilities with similar typologies.